Encouraging legibility and comprehensibility through multimodal patient information guides - Prieto-Velasco, Juan Antonio; Montalt-Resurrecció, Vicent (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
Medical texts intended for patients are a key instrument in doctor–patient communication. Through a process of heterofunctional translation, they can be adapted to the needs and expectations of their recipients. Most techniques aimed at making reading and understanding easier are linguistic in nature, and little attention has been paid to the role played by visuals. Through a questionnaire and a focus group, this pilot study explored patients’ perception and reception of images in a patient information guide. Our main finding was that visuals depicting medical concepts can be graphical support for unfamiliar concepts and encourage comprehension of texts aimed at patients. The most useful type of visual appears to be simplified images describing concepts with clarity and preventing recipients from recalling unpleasant experiences.